Prevalence and associations of steep Cornea/Keratoconus in greater Beijing: the Beijing Eye Study - Xu, Liang; Jonas, Jost B. (PLOS ONE, 2012)
Purpose To evaluate the prevalence and associated factors of steep cornea/keratoconus in the adult Chinese population. Methods The population-based Beijing Eye Study 2011 included 3468 individuals with a mean age of 64.6±9.8 years (range: 50-93 years). A detailed ophthalmic examination was performed including optical low-coherence reflectometry. Steep cornea/keratoconus were defined as an anterior corneal refractive power exceeding 48 diopters. Results Mean refractive power of the cornea was 43.16±1.45 diopters (range: 36.51 to 48.46 diopters; flattest meridian) and 43.98±1.52 diopters (range: 37.00 to 52.88 diopters; steepest meridian). A steep cornea/keratoconus defined as corneal refractive power of ≥48 diopters and ≥49 diopters was detected in 27 subjects (prevalence rate: 0.9±0.2%) and 6 (0.2± 0.1%) subjects, respectively. Presence of steep cornea/keratoconus was associated with shorter axial length (P<0.001), smaller interpupillary distance (P = 0.038), lower best corrected visual acuity (P = 0.021), higher cylindrical refractive error (P<0.001) and more myopic refractive error (P<0.001). It was not significantly associated with gender, body height, psychic depression, cognitive function, blood concentrations of glucose, lipids, creatinine and C-reactive protein, blood pressure and quality of life score, nor with intraocular pressure, dry eye feeling, and lens thickness. Conclusions A steep cornea/keratoconus defined as corneal refractive power of 48+ diopters has a prevalence of 0.9±0.2% among Chinese aged 50 years and above. Its prevalence was significantly associated with the ocular parameters of shorter axial length, smaller interpupillary distance, higher cylindrical and myopic refractive error and lower best corrected visual acuity, however, with none of the systemic parameters tested.